2009
DOI: 10.1073/pnas.0908874106
|View full text |Cite
|
Sign up to set email alerts
|

Absence of geochemical evidence for an impact event at the Bølling–Allerød/Younger Dryas transition

Abstract: Os isotopes ͉ platinum group elements ͉ Clovis ͉ Pleistocene extinction ͉ meteorite P roxy records of millennial-scale climate variations during the most recent deglaciation from polar ice cores (1-3) as well as deep-sea and lacustrine sediments (4-10) display abrupt changes that are typically attributed to internal forcing of Earth's climate system. A striking example is the Younger Dryas (YD) cooling episode from 12.896 Ϯ 0.138 thousand years (ka) to 11.703 Ϯ 0.099 ka calendar years before AD 2000 (11) after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 73 publications
6
61
0
1
Order By: Relevance
“…S1), which points strongly toward a terrestrial (upper crustal) source. This finding is similar to that of Paquay et al (13), who analyzed platinum group elements and osmium isotopes in Younger Dryas (YD)-age sediments from different depositional settings and arrived at the same conclusion. If the iridium is carried in the magnetic sediments, as it appears to be based on Firestone et al's data (1), then the REE results imply that the iridium likely has a terrestrial origin as well.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…S1), which points strongly toward a terrestrial (upper crustal) source. This finding is similar to that of Paquay et al (13), who analyzed platinum group elements and osmium isotopes in Younger Dryas (YD)-age sediments from different depositional settings and arrived at the same conclusion. If the iridium is carried in the magnetic sediments, as it appears to be based on Firestone et al's data (1), then the REE results imply that the iridium likely has a terrestrial origin as well.…”
Section: Discussionsupporting
confidence: 90%
“…(Note that Ir bs was measured on bulk samples of 10 g or larger to avoid any "nugget effects"; ref. 13). The highest concentrations were found in an 8.2 ka black mat at Tilomonte (1.20 AE 0.21 ppb), a 10.6 ka mat at Quebrada Agua de Cascabel (QAC 4; 0.86 AE 0.21 ppb), a 13.0 ka mat at El Salto 1 (1.65 AE 0.10 ppb), and a >40 ka mat at Rio Salado (2.51 AE 0.15 ppb).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18-21. Many of the impact markers reported in YD black mats have been widely discredited (22)(23)(24)(25)(26)(27) with the exception of the enigmatic nanodiamonds.…”
Section: Uring the End Of The Last Glacial Period In The Northernmentioning
confidence: 99%
“…In North America and the Middle East, Bunch et al (2012) identified YDB melt-glass that formed at high temperatures (1730Њ to 12200ЊC), as also reported by three independent groups, Mahaney et al (2010) in South America and Fayek et al (2012) and Wu et al (2013) in North America. This study focuses solely on nanodiamonds (NDs), and so, for independent discussions of other proxies, see Haynes et al (2010) and Paquay et al (2009), who found no evidence for the platinum-group elements iridium or osmium. Alternately, Wu et al (2013) found large YDB anomalies in osmium, as discussed below.…”
Section: Introductionmentioning
confidence: 99%